Contratos empresariais de longa duração e incompletude contratual - Faganello, Tiago (2017)
The present dissertation has the objective of analyzing long-term commercial contracts that have contractual gaps (lacunae), especially through the literature of Law and Economics. In scenarios of perfect competition, contracts would be able to foresee all contingencies and perfect state of nature. However, real markets do not reflect the perfect competition model and, as such, as there may be gap in the legal system (article 4 of the Law of Introduction to Brazilian Law), there are situations in which there may be gap in the contract drafted by the parties to serve a particular purpose. Contracts that contain such lacunae are known as incomplete contracts, and these omissions may be voluntary or involuntary. Thus, initially, the first part of this dissertation will establish a general framework of contracts and their relations to the economy and the market. Following, the concept of long-term corporate contracts will be analyzed and the impossibility of predisposition of all future contingencies and allocation of all existing risks in the contract, that is, the recognition that such contracts have lacunae and, consequently, are incomplete. In the second part of this dissertation, the concept of incomplete contracts will be analyzed, as well as its sources and manners for the solution of such contractual incompletion. Finally, on the last part of the second session, a modality of ascertainment of lacunae that seeks to preserve contractual ties in the event of conflict will be described, namely, renegotiation.